The Use of hCG for Inducing Ovulation in Sheep Estrus Synchronization Impairs Ovulatory Follicle Growth and Fertility - Bruno Galarraga, María Macarena; Cano Moreno, Virginia; Lago Cruz, Beatriz; Encinas, Teresa; Gonzalez Bulnes, Antonio; Martinez Ros, Paula (MDPI, 2021)
Currently, there is an intense effort to find an alternative hormone to eCG to induce ovulation after estrus synchronization treatments in sheep. One of the proposed alternatives is based on the use of hCG, but the results are controversial since fertility rates are commonly affected. The present study aims to evaluate, therefore, the adequacy of hCG in protocols for the synchronization of estrus and ovulation. Ovarian follicle dynamics, occurrence of estrus behavior and subsequent ovulation, quality of corpora lutea, and pregnancy rate after controlled natural mating were assessed in two consecutive trials. The findings indicate that the low fertility rates reported for the protocols based on the administration of hCG for inducing ovulation during estrus synchronization in sheep may be related to a high occurrence of abnormal follicular growth patterns, disturbances, and retardments of ovulation and concomitant formation of follicular cysts in the treated females. These results preclude their practical application to induce ovulation concomitantly to estrous synchronization treatments.